Ji Hye Jung, percussion - Colorado State University. Department of Music, producers (managers) (Colorado State University. Libraries, 2014)
Date on program is incorrect, January 28, 2013 should be January 28, 2014.
Special guest: Ji Hye Jung, percussion
Virtuoso series
Keywords: Ji Hye Jung (Organ Recital Hall, 2014)